Sustainable green tea production through agroecological management and land conversion practices for restoring soil health, crop productivity and economic efficiency: Evidence from Northern Vietnam - Viet San Le; Laetitia Herrmann; Lambert Brau; Lesueur, Didier (Wiley, 2023)
Tea is a very important cash crop in Vietnam as it provides crucial income and employment for farmers in poor rural areas. Unfortunately, the dominance of long-term, conventional tea cultivation has caused severe soil health degradation and environmental pollution. At the same time, as tea production may provide a better net income compared with other annual crops such as rice and vegetables, farmers have been converting parts of their allocated land to cultivate tea plants. Little is known about the benefit of agroecological management as an alternative to conventional tea management practices, and thus, there is a need to understand how it can improve tea yields, quality and the livelihoods of the farmers. Conducted in Northern Vietnam from 2019 to 2022, this study examined the impacts of agroecological tea management practices on soil health indicators, tea yield and quality, and net income of tea farmers. We showed that agroecological management practices significantly enhanced soil organic matter by 0.8% and soil pH by 0.5 units on average. Conversely, conventional management based on chemical fertilizer applications, significantly increased soil total nitrogen by 0.15%–0.2%. No significant differences were observed between soil texture and other soil chemical characteristics. Soil biological parameters were also significantly higher in agroecological tea soil and root samples than in conventional tea plots. Average AMF frequency and intensity of the agroecological tea roots were 98% and 37%, respectively, compared with 73% and 15% of the conventional tea roots. Likewise, soil macrofauna and mesofauna abundance in the agroecological tea lantations was 76 individuals/m2 and 101 individuals/100 g fresh soil on average, respectively, while that of conventional tea farms were 34 and 63 individuals/100 g fresh soil, respectively. Interestingly, a comparison between the converted and nonconverted lands did not show any significant effect of the conversion on soil physicochemical and biological characteristics, apart from tea root AMF colonization. Conventional tea management consistently resulted in higher tea yield and yield components, even though the differences were not always statistically significant. Despite lower tea yields, agroecological tea adopters earned around USD 8400 ha/year more than the farmers still practicing conventional management. This study shows that it is economically and environmentally more sustainable to produce organic tea than conventional tea, and our results should encourage more farmers to adopt such agroecological practices in Northern Vietnam.